HUBUNGAN PEMANFAATAN AIR SUNGAI DENGAN KEJADIAN GEJALA DERMATITIS - Samuel Marganda Manalu; Astrie Kartika Putri (Jurnal Penelitian Kesmasy, 2019)
The purpose of this study was to look the relationship between river water utilization with the incidence of dermatitis symptoms in the village of Lantasan Lama, Patumbak District, Deli Serdang Regency. This research was analytical with cross-sectional research design, which is to find out the relationship between river water utilization with the incidence of dermatitis in the village of Lantasan Lama, Patumbak District, Deli Serdang Regency. The population of this study were housewives who used river water that was totaling 108 respondents with purposive sampling. The data used primary and secondary data. Data were analyzed by using the chi-square test. The results showed that the largest percentage based on the age of the respondents was at the age of 36-45 years. The largest percentage based on respondent's education was high school education. River users used river water were quite bad. River users use river water with the largest percentage of washing. River users mostly got dermatitis symptoms. There was a relationship between river water utilization and the incidence of dermatitis (p-value = 0.001). It is hoped that the peoples around Lantasan Lama river increase their knowledge about their habits that can pollute Lantasan Lama River and it can caused symptoms of dermatitis and change their behavior to better one.